Medical Usage of Degradable Shape Memory Polymers - Liu, Hongyi (Transactions on Environment, Energy and Earth Sciences, 2026)
In recent years, with the emergence of a large number of research results on degradable Shape Memory Polymers (dSMPs), some researchers have noticed that this material has a wide range of application scenarios in medicine. This article summarizes the current application status of different types of shape memory materials in various fields of medicine and reflects their application value in medicine. Research has found that dSMPs have already found certain applications in implants. Due to their unique advantages, they are gradually replacing implants made of traditional materials. However, there is less research on them in the field of micro-robots, and they still have broad research prospects. Compared with traditional materials, the special properties of dSMPs enable it to break through the constraints of original thinking in medicine, no longer limited by factors such as shape and volume, and design more complex, advanced and complete medical devices, exerting a profound and extensive influence on the development of medicine.